Two‐factor authentication using biometric based quantum operations. Issue 3 (2nd January 2020) - Sharma, Mohit Kr; Nene, Manisha J
Abstract: Two‐way authentication methods are utilized in every online user authentication transactions. Use of one time passwords (OTP) have proved to be more secure method, than one factor authentication when the two authentication schemes are carried out on different media. However, current use of OTP restricts authentication to the device itself rather than the user. The fraud cases with OTP based transactions have also increased due to growth of technology. Hence, there is a requirement of enhancing security of OTP based transactions. The study in this paper anchors on mathematically proven properties of quantum cryptography and utilizes the quantum entanglement property to generate quantum OTP ( QOTP ) for authenticating the user based on its biometrics. The proposed method takes into consideration various quantum computing capabilities of user, thus paving path for gradual upgradation of infrastructure. The work in the paper gives the outline of infrastructure required for implementing the proposed model and concludes by comparing security analysis of existing and proposed model against man‐in‐the‐middle attack (MITM) and user end vulnerabilities to bring forth the importance of QOTP. The practical implementation of the proposed model is envisaged as future research work due to evolving nature of quantum experiments.